Energy Efficiency in Production Machines Through Harmonic Distortion Reduction - Ju, Shu; Hanenkamp, Nico (IEEE PES Asia-Pacific Power and Energy Engineering Conference, 2019)
With the growing trend towards massive utilization of power electronics, the effect of harmonic distortions on not only power grids but only other system components is non-negligible. In this document, the source and effect of harmonic distortions are described. Latest state of harmonic distortion reduction technologies was researched and briefly depicted. Because of the technological limitations of the current methods, a control strategy by adjusting motor speed change trajectories in order to generate less harmonic distortions in motor acceleration and deceleration processes has been developed. The implementation needs only control software changes and no hardware installation. Based on sufficient simulation results, experiments have been carried out on a lab-constructed motor test bench. Optimized motor speed change trajectories with time-delayed transfer elements have been adjusted and put into operation, ensuring up to 20% energy saving potential during the motor speed changing phases. Energy efficiency can be achieved by applying the optimization method to any use case of power electronic actuators characterized by a highly dynamic machining proces
Keywords: Energy efficiency; harmonic distortion; machining; optimization methods; variable frequency drives